1988
DOI: 10.1177/002580248802800217
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Traffic Safety of Introducing a 0.05% Blood Alcohol Level in Queensland, Australia

Abstract: A 0.08% maximum legal blood alcohol level (BAL) for drivers in Queensland was replaced by a 0.05% BAL. As alcohol is especially likely to be a factor in night-time accidents, the evaluation focused on the extent to which night-time accidents decreased in comparison to daytime accidents. It appeared that most, if not all, of the significant 8.2% reduction in night-time hospitalization and 5.5% reduction in property damage accidents in the first year after the legislative change could be attributed to the lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Research design Main findings Vingilis et al (1988) Ontario, Canada Administrative .05% BAC law (178) Short-term decrease-from 59% to 32%-in the proportion of drivers with a positive BAC Control series did not display significant decrease for the period under study (p-values are not reported) Smith (1988) Queensland, Austrlia Administrative .05% BAC law introduced on December 1st1982…”
Section: Authors Jurisdiction and Measuresmentioning
confidence: 99%
“…Research design Main findings Vingilis et al (1988) Ontario, Canada Administrative .05% BAC law (178) Short-term decrease-from 59% to 32%-in the proportion of drivers with a positive BAC Control series did not display significant decrease for the period under study (p-values are not reported) Smith (1988) Queensland, Austrlia Administrative .05% BAC law introduced on December 1st1982…”
Section: Authors Jurisdiction and Measuresmentioning
confidence: 99%
“…In both the Grand Rapids [z6] and Adelaide [2o] case control studies, drivers with a BAC between o.o 5 and o.o8% were significantly more likely to be in a crash than a control group of comparison drivers below o.o5%. Evaluations of the introduction of a o.o5% BAC in New South Wales and Queensland [75,76 ] have shown crash reduction benefits of the lower BAC level in comparison to o.o8 BAC. Lower BAC's also realized significant financial savings in both states.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence is consistent and persuasive that fatal and injury crashes involving drinking drivers decrease at least 5% to 8% and up to 18% after a country lowers its illegal BAC limit from 0.08 to 0.05 g/dL BAC. [88][89][90][91] If all U.S. states were to adopt the 0.05 g/dL BAC standard and it were enforced, an estimated 500 to 800 lives could be saved each year. 92 Moreover, it can easily be argued that setting a 0.05 g/dL BAC is a reasonable standard.…”
Section: Ed-based Alcohol Screening and Brief Interventionsmentioning
confidence: 99%